2021
DOI: 10.15503/jecs2021.1.103.116
|View full text |Cite
|
Sign up to set email alerts
|

Apple Tree Model of Emotion-Involved Processing: Videos for Emotions and Foreign Language Learning

Abstract: Aim. The primary aim of this paper is to present and discuss the Apple-Tree Model of Emotion-Involved Processing in the context of foreign language learning with regard to didactic, neuroscientific, and psychological viewpoints. The proposed model mirrors theories which emphasize the role of emotional experiencing in the process of learning and relate it to the enhancement of cognitive processes. The secondary aim of this paper is to propose examples of application of these theories and recent research finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Another indication in this regard is that EFL students, usually with a tight schedule and demanding tasks on developing comprehensive language and intercultural communication skills, might consciously develop their ER abilities especially reappraisal for the aim of achieving enjoyment of FL learning. This is also in line with the previous study which discovered a positive impact of emotional engagement on language learning, as for proactive and reluctant learners alike, if they can be emotionally engaged in the course, they would be more likely to achieve higher motivation in an FL learning context [78].…”
Section: Discussionsupporting
confidence: 92%
“…Another indication in this regard is that EFL students, usually with a tight schedule and demanding tasks on developing comprehensive language and intercultural communication skills, might consciously develop their ER abilities especially reappraisal for the aim of achieving enjoyment of FL learning. This is also in line with the previous study which discovered a positive impact of emotional engagement on language learning, as for proactive and reluctant learners alike, if they can be emotionally engaged in the course, they would be more likely to achieve higher motivation in an FL learning context [78].…”
Section: Discussionsupporting
confidence: 92%
“…Bernstein, 2010) but also what has been called for in second language acquisition (SLA) research; SLA theories and research are expected to be helpful to teachers and students, addressing practical problems (Ellis, 2021). In accordance with this epistemology, Kamenická's (2021) Apple Tree Model is an interesting attempt to dilate the didactic horizons of the Emotion-Involved Processing Hypothesis. 5.…”
Section: Fundingmentioning
confidence: 99%
“…Kanazawa (2021) empirically showed that Emotion-Involved Processing results in better long-term 2 retention than non-emotional semantic processing, supporting the EIPH. The EIPH along with its tripartite levels of processing was further extended by Kamenická's (2021) Apple Tree Model, dilating the didactic horizons of EIPH. Indeed, the implication and the potentiality of EIPH as a psychophilosophical model goes beyond the domain-specific paradigm of vocabulary memory.…”
Section: Introductionmentioning
confidence: 99%